Offering prosocial incentives on-top: Do they sweeten the deal or poison the well? - Sven Beisecker; Christian Schlereth (Psychology & Marketing, 2023)
Companies often rely on customer feedback to build and improve their business. Customers, in turn, are expected to (i) fill in customer feedback surveys (participation) and (ii) provide accurate responses (performance). To encourage active participation and ensure accurate responses, companies traditionally offer either self-benefiting incentives, like lottery prizes, or prosocial incentives, like charity donations. More recently, some companies have started offering prosocial incentives on top of self-benefiting incentives in the hope to “sweeten the deal,” that is, to improve participation and performance even further. With this research, we challenge whether the on-top prosocial incentives are effective. The evidence from two field experiments and one incentive-aligned online experiment does not confirm any such advantage. In contrast, performance can decrease when a low-amount on-top prosocial incentive is offered relative to a pure self-benefiting setting. This trend is only reversed once the on-top incentive amount increases. Furthermore, for participation, we find that on-top prosocial incentives are ineffective and, at higher amounts, even detrimental. Therefore, our empirical insights rather suggest that on-top prosocial incentives “poison the well.”
Keywords: 650; affective value; lottery; performance; prosocial incentives